APLIKASI KEAMANAN SMS MENGGUNAKAN ALGORITMA RIJNDAEL - Raisul Azhar; Kurniawan Kurniawan (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2016)
Mobile phones and smartphones providing the basic features of SMS (Short Message Service). Messages sent through SMS facility sometimes confidential, so that the necessary mechanisms to protect messages from crime. Mechanism that can be used to protect the message is to use a cryptographic algorithm Rijndael. This algorithm is a cryptographic algorithm chipher 128-bit block that has the ability to protect confidential messages. This research resulted in an application that can be used to protect the SMS message when the message is sent and received by users. Based on research conducted on the length of different messages with the same key length is obtained that the length of the message used computing time takes longer than the length of the message is the same and different key lengths.